Um estudo do impacto do draft nas temporadas posteriores da NFL - Martins, Matthews Luiz Muniz (Universidade Federal de São Carlos, 2024)
The National Football League (NFL) is the world’s premier American football league, consisting of 32 teams divided into two conferences and organized into offensive, defensive, and special teams units. Unlike traditional soccer leagues, the NFL operates a management system designed to benefit lower-performing teams, aiming to balance competition and reduce the predictability of outcomes. One of the main mechanisms to ensure competitiveness is the Draft, a selection process that allows teams to choose new players based on a system that favors teams with weaker performances in the previous season. This study seeks to establish procedures to evaluate the impact of the Draft on team performance in subsequent years. Descriptive and multivariate methods (Principal Component Analysis (PCA)) were applied to analyze NFL season data from 2002 to 2022. These methods helped identify relationships between the variables in the study and their behavior in relation to overall team performance and the performance of rookie players over time. PCA was also used to evaluate the relationship between the level of investment teams made in the Draft and their future performance. The results obtained throughout the study demonstrated that the NFL Draft has a significant impact on teams, regardless of their initial performance level, influencing both their present and future results..
A study of the impact of the draft on subsequent NFL seasons
Keywords: Análise de componentes principais; Draft; Futebol americano; NFL; ACP; Principal components analysis; American football; PCA; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::PROBABILIDADE E ESTATISTICA APLICADAS